Seleksi Pemakalah Terbaik Dalam Acara Seminar Nasional Pada Universitas Budi Darma Medan Dengan Sistem Pendukung Keputusan Menerapkan Metode Aras Dan Borda - Diana Sari (STMIK Budi Darma, 2022)
The problem in selecting the best presenter is that the SENSASI seminar organizing committee at the Budi Darma University campus has difficulty in making decisions to determine the best presenter where the assessment process is objective based on several different criteria and different weighting of the assessment, causing errors in the final decision making in this matter. Therefore, in order to solve the problems experienced by the organizing committee of the national seminar which was held at the Budi Darma University campus, Medan. Therefore, a decision support system is needed to select the best presenter. In selecting a method, using the ARAS & BORDA method, this system will get the results of ranking decisions made based on each alternative choice according to the many criteria set. The alternative with the greatest weight is the recommended alternative. To implement a decision support system, a decision support system application is designed. The design is made using the Visual Basic 2008 application, this application is designed simply to make it easier for users, with the application of this decision support system it is hoped that it can facilitate the national seminar organizing committee in selecting the best pemakalahl so that the selection of the best presenter gets the results as expected.